صيغة "استفعل" ومشتقاتها الفعلية فيما تفرد به الإمام مسلم (ت ٢٦١هـ) في صحيحه (دراسة صرفية دلالية): Morphological and Semantic Analysis of the Form “استفعل” and Its Verbal Derivatives in the Exclusive Narrations of Imam Muslim (d. 261 AH) in His Sahih - Hafiz Fasih Ur Rehman (Al Manhal Research Journal, 2025)
This article examines the morphological and semantic features of verbs in the word istaf’ala (استفعل) and their derivatives in Hadith uniquely reported by Imam Muslim in his book Sahih Muslim. Using a descriptive-analytical method, the study analyzes selected Hadith examples to identify the words and contextual meanings of istaf’ala (استفعل). The results show that these verbs can convey several meanings, such as requesting (الطلب), adopting (الاتخاذ) and others. Its precise use in Hadith language helps deepen the understanding of Prophetic speech and highlights its richness in both expression and meaning.